Gut Microbiota Composition Is Associated With the Global DNA Methylation Pattern in Obesity - Ramos-Molina, Bruno; Sánchez-Alcoholado, Lidia; Cabrera-Mulero, Amanda; Lopez-Dominguez, Raul; Carmona-Saez, Pedro; Garcia-Fuentes, Eduardo; Moreno-Indias, Isabel; Tinahones, Francisco J. (Frontiers in Genetics, 2019)
Objective: Obesity and obesity-related metabolic diseases are characterized by gut microbiota and epigenetic alterations. Recent insight has suggested the existence of a crosstalk between the gut microbiome and the epigenome. However, the possible link between alterations in gut microbiome composition and epigenetic marks in obesity has been not explored yet. The aim of this work is to establish a link between the gut microbiota and the global DNA methylation profile in a group of obese subjects and to report potential candidate genes that could be epigenetically regulated by gut microbiota in adipose tissue. Methods: Gut microbiota composition was analyzed in DNA stool samples from 45 obese subjects by 16S rRNA gene sequencing. 20 patients were selected based on their Bacteroidetes-to-Firmicutes ratio (BFR): HighBFR group (BFR>2.5, n=10); LowBFR group (BFR<1.2, n=10). Genome-wide analysis of DNA methylation pattern in both whole blood and visceral adipose tissue of these selected patients was performed with an Infinium EPIC BeadChip array-based platform. Gene expression analysis of candidate genes was done in adipose tissue by real-time quantitative PCR. Results: Genome-wide analysis of DNA methylation revealed a completely different DNA methylome pattern in both blood and adipose tissue in the low BFR group vs. the high BFR group. 258 genes were differentially methylated in both blood and adipose tissue, of which several potential candidates were selected for gene expression analysis. We found that in adipose tissue both HDAC7 and IGF2BP2 were hypomethylated and overexpressed in the low BFR group compared to the high BFR group. β values of both genes significantly correlated with the BFR ratio and the relative abundance of Bacteroidetes and/or Firmicutes. Conclusions: In this study we demonstrate that the DNA methylation status is associated to gut microbiota composition in obese subjects, and that the expression levels of candidate genes implicated in glucose and energy ho meostasis (e.g. HDAC7 and IGF2BP2) could be epigenetically regulated by gut bacterial populations in adipose tissue.